Serum F2-Isoprostane Levels in Preterm Deliveries Compared to Normal Preterm Pregnancies - Hartono, Johannes (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the difference between serum F2-isoprostane levels in women with preterm deliveries compared to women in normal preterm pregnancies. Method: Our study is a cross sectional study. During the period of January to August 2012, we collected 72 samples in the Emergency Department and Obstetrics and Gynecology outpatient clinic of Sanglah hospital, Denpasar. Our sample was divided into two groups, 36 cases of preterm deliveries at 28-37 weeks gestational age and 36 preterm normal pregnancies at 28-37 weeks gestational age. We collected 3 ml of blood sample from the cubital vein and quantified the F2-isoprostane levels at the Biology Molecular Laboratory, Faculty of Medicine University of Udayana, Denpasar. Data was analyzed using the Shapiro Wilk test and independent t-test with significance of =0.05. Result: The mean F2-isoprostane level for preterm deliveries and preterm normal pregnancies were 0.315 0.292 pg/ml and 0.017 0.018 pg/ml. Conclusion: We can conclude from this study that there is a difference in F2-isoprostane serum level in preterm labor and normal preterm pregnancies. [Indones J Obstet Gynecol 2014; 4: 182-184] Keywords: F2-Isoprostane, normal preterm pregnancy, preterm delivery